Monitoring recombinant protein expression in bacteria by rapid evaporative ionisation mass spectrometry. (18th February 2020) - Sarsby, Joscelyn; McLean, Lynn; Harman, Victoria M.; Beynon, Robert J.
Abstract : Rationale: There is increasing interest in methods of direct analysis mass spectrometry that bypass complex sample preparation steps. Methods: One of the most interesting new ionisation methods is rapid evaporative ionisation mass spectrometry (REIMS) in which samples are vapourised and the combustion products are subsequently ionised and analysed by mass spectrometry (Synapt G2si). The only sample preparation required is the recovery of a cell pellet from a culture that can be analysed immediately. Results: We demonstrate that REIMS can be used to monitor the expression of heterologous recombinant proteins in Escherichia coli . Clear segregation was achievable between bacteria harvesting plasmids that were strongly expressed and other cultures in which the plasmid did not result in the expression of large amounts of recombinant product. Conclusions: REIMS has considerable potential as a near‐instantaneous monitoring tool for protein production in a biotechnology environment.